2021
DOI: 10.1186/s12893-020-00987-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of the supraclavicular artery island flap for reconstruction of maxillofacial defects: a case report and literature review

Abstract: Background Free flaps are widely used in maxillofacial reconstruction; however, this approach was not feasible in the current case. It was not possible because the free flap method requires microvascular anastomosis expertise, which is difficult, time-consuming and costly. Case presentation An 86-year-old woman suffered squamous cell carcinoma on the right side of her face, which resulted in a large soft-tissue defect. Here, we present a case of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Despite the advances in the use of the locoregional flaps, some complications as ischemia can occur after the transfer of the flap due to tissue hypoperfusion resulting in partial or complete loss of the flap (10). Given the rise in the incidence of maxillofacial cutaneous malignant neoplasia, the provision of satisfactory treatment to repair the resulting facial defects can pose a significant surgical challenge (11). In the past two decades, previous studies have demonstrated the reliability of supraclavicular artery island flap (SCAIF) for refractory defects from trauma, medication/radiation-induced osteonecrosis, and cancer ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advances in the use of the locoregional flaps, some complications as ischemia can occur after the transfer of the flap due to tissue hypoperfusion resulting in partial or complete loss of the flap (10). Given the rise in the incidence of maxillofacial cutaneous malignant neoplasia, the provision of satisfactory treatment to repair the resulting facial defects can pose a significant surgical challenge (11). In the past two decades, previous studies have demonstrated the reliability of supraclavicular artery island flap (SCAIF) for refractory defects from trauma, medication/radiation-induced osteonecrosis, and cancer ablation.…”
Section: Introductionmentioning
confidence: 99%